Clonal diversity of Escherichia coli isolates from marketed beef in East Malaysia - K, Apun; PP, Chang; EUH, Sim; V, Micky (Springer Netherlands, 2006)
Escherichia coli, including Shiga-like toxin producing E. coli (STEC), serogroup O157:H7 and E. coli O157, were isolated from raw beef marketed in Sarawak and Sabah, East Malaysia. Molecular subtyping by pulsed-field gel electrophoresis (PFGE) was performed on 51 confirmed E. coli isolates. Of the 51 isolates, five were E. coli O157:H7, four E. coli O157, two non-O157 STEC and 40 other E. coli isolates (non-STEC). Digestion of chromosomal DNA from these E. coli isolates with restriction endonuclease XbaI (5′-TCTAGA-3′), followed by PFGE, produced 45 restriction endonuclease digestion profiles (REDPs) of 10–18 bands. E. coli O157:H7 isolates from one beef sample were found to have identical PFGE profiles. In contrast, E. coli serogroup O157 from different beef samples displayed considerable differences in their PFGE profiles. These suggested that E. coli isolates of both serogroups were not closely related. A large variety of PFGE patterns among non-STEC isolates were observed, demonstrating a high clonal diversity of E. coli in the beef marketed in East Malaysia. The distance matrix values (D), calculated showed that none of the pathogenic E. coli strains displayed close genetic relationship with the non-STEC strains. Based on the PFGE profiles, a dendrogram was generated and the isolates were grouped into five PFGE clusters (A–E). From the dendrogram, the most related isolates were E. coli O157:H7, grouped within cluster B. The STEC O157:H7 beef isolates were more closely related to the clinical E. coli O157:H7 isolate than the E. coli O157:H7 reference culture, EDL933. Cluster A, comprising many of other E. coli isolates was shown to be the most heterogeneous. PFGE was shown to possess high discriminatory power in typing pathogenic and non-pathogenic E. coli strains, and useful in studying possible clonal relationship among strains.